(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores how two culturally distant yet philosophically parallel authors—Pirimqul Qodirov from Uzbekistan and Ian McEwan from the United Kingdom—represent historical consciousness and the ethics of memory in their novels Yulduzli Tunlar (Starry Nights) and Atonement. The study focuses on how personal guilt, collective responsibility, and historical truth intersect within their narratives. While Qodirov reconstructs national identity through the figure of Babur, McEwan reimagines personal morality through Briony’s internal struggle for redemption. The comparative approach demonstrates that both writers, though shaped by different civilizations and ideologies, use literature to preserve moral awareness and challenge the reader to reflect on history as a living ethical process.